Glycine ester ionic liquid as new co‐initiator used in initiating radical and cationic photopolymerization. Issue 8 (19th May 2022) - Nan, Xuying; Luo, Youping; Wu, Mingshu; Chen, Guangying
Abstract: Ionic liquids using amino acid ester as cations is a new generation of green ionic liquids. It is found for the first time that they can be used as co‐initiators to initiate radical photopolymerization in the presence of commercial type II sensitizer, camphorquinone (CQ) under mild irradiation conditions. To intensively investigate this new function, we synthesized a series of glycine ester ionic liquids by a very simple method, and then evaluated their performance as co‐initiators in radical photopolymerization. The polymerization studies show that their co‐initiation abilities depend strongly on the structures of N‐terminal substituents and ester groups, as well as the type of anion moiety. And the pH values of the formula also have a heavy influence on their performances. More interestingly, when a small amount of hydroxyethyl acrylate (HEA) was added, under irradiation this multicomponent system composed of CQ, ionic liquids when anion moiety is PF6 −, BF4 − or SbF6 −, and HEA, can release H + to initiate cationic polymerization. These facts demonstrated that the investigated glycine ester ionic liquids can be considered as valid, environmentally friendly alternatives to toxic aromatic amines co‐initiators. Besides, the corresponding photoinitiation mechanism is suggested. Abstract : Radical/Cationic photopolymerization initiated by Glycine ester ionic liquids as co‐initiator.